The elusive unified field theory? - Gall, Clarence (Rev. Téc. Fac. Ing. Univ. Zulia)
The proposal that the Einstein field equations (Rµï³ = O) originally conceived solely for the gravitational field in a matter free region of space, actually constitute a possible set of unified field equations is re-examined. The thought process involved in arriving at this conclusion is shown to imply a ";multiplicative’ approach to the description of matter. Line elements for free space and for an isotropic medium both in a spherically symmetric gravitational field, that are wavelength and frequency dependent with respect to electromagnetic radiation, are introduced and their significance is discussed.